Comparison of rare earth element geochemistry and Nd isotopes in two adjacent tropical estuaries: Van Uc and Cam-Nam Trieu, Northern Vietnam - Pham, Quoc Viet; Vinh, Vu Duy; Ouilon, Sylvain; Jeandel, Catherine (Vietnam Journal of Marine Science and Technology, 2025)
Concentrations of rare earth elements (REE) were measured in surface waters collected from the Van Uc and Cam estuaries, from the inner river to the estuarine transition zone. Additionally, the neodymium isotope composition (Nd-IC) of two river water samples was analyzed to compare the two adjacent rivers under different geochemical conditions and anthropogenic influences. Water samples were preconcentrated using Nobias® resin prior to REE analysis by Sector Field-ICP-MS, while Nd-IC measurements were performed on a Thermal Ionization Mass Spectrometer (TIMS) after several treatments. The total REE concentrations (ƩREE) in the Van Uc estuary ranged from 10.5 to 23.6 nmol/kg, significantly higher than those in the Cam-Nam Trieu estuary, which ranged from 2.14 to 6.34 nmol/kg. Both Van Uc and Cam riverine and estuarine water are enriched in the middle REE (MREE) relative to light REE (LREE), with depletion observed in heavy REE (HREE) when normalized to shale compositions. No negative cerium anomalies (Ce*/Ce) were observed in any sample, reflecting the predominance of riverine influence in the estuarine mixing zone. Gadolinium anomalies (Gd*/Gd) were uniformly positive but low (≤ 1.3), implying minimal inputs from gadolinium-based MRI contrast agents or sufficient dilution to suppress detectable anthropogenic Gd signals. Nd-IC of the Van Uc water was εNd = -10.5 while of Cam-Nam Trieu water was less radiogenic, with εNd = -11.3.